Coaching on Alternative Animal Feed by Rice Straw Fermentation in Tlogowarak, Giripurwo, Purwosari, Gunungkidul - Adib Abbiya Qowiyyudin; Fajar Azis Utama; Santi Ria Lailatul Muktamaroh; Anisa Isdiyanti; Heri Setiyawan; Mira Nurrohlistiani; Ibadur Rahman; Akvina Khoirunisa; Lolo Nara Suryana (Kaunia: Integration and Interconnection Islam and Science, 2019)
This community service was carried out in the farming community and cattleman in Tlogowarak, Giripurwo Village, Gunungkidul Regency. This service was carried out through Direct Coaching and Training activities to the local society. It is aimed to utilize probiotic fermentation technology to increase the value of farmers' rice straw as an alternative feed for cattle and goats in Tlogowarak, Giripurwo, Gunungkidul. Through this service, it is expected that farmers and cattleman have knowledge and skills about bio-fermentation technology to increase the nutritional value of rice straw with the help of molasse bacteria (local microorganisms) or by mixing liquid molasses and EM4 (Effective Microorganism 2-4). The results showed that the knowledge and skills of the farmers and cattleman of Tlogowarak about the bio-fermentation technique are increase after training program, so they were able to process the straw waste into an alternative feed for livestock so that could help farmers in lack of grass in the dry season.